2019
DOI: 10.1021/acs.jafc.9b02782
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue Determination of 27 Sulfonamides in Poultry Feathers and Its Application to a Sulfamethazine Pharmacokinetics Study on Laying Hen Feathers and Sulfonamide Residue Monitoring on Poultry Feathers

Abstract: A method for the simultaneous determination of 27 sulfonamides in poultry feathers using ultra performance liquid chromatography−tandem mass spectrometry (UPLC−MS/MS) was established in this study. The samples were extracted using 0.1 mol/L HCl solutions in a 60 °C water bath for 2 h, purified using hydrophilic−lipophilic balance solid-phase extraction, nitrogen-dried, and then reconstituted for UPLC−MS/MS analysis, which was performed with a CSH-C18 column. Linearity, limit of detection, limit of quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For example, Dimitrios B et al found that sulfonamides not only induce drug-resistant bacteria in human intestinal flora but also lead to abnormalities including those of the liver and kidneys [ 3 ]. To safeguard public health, the permissible limits of sulfonamides in food (e.g., bread, eggs, and milk) and feed established by the EU, US-FDA, and China are 100 μg/kg [ 4 ]. Unfortunately, sulfonamides are a growing cause of health concern because of its high levels in edible agricultural and food products [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dimitrios B et al found that sulfonamides not only induce drug-resistant bacteria in human intestinal flora but also lead to abnormalities including those of the liver and kidneys [ 3 ]. To safeguard public health, the permissible limits of sulfonamides in food (e.g., bread, eggs, and milk) and feed established by the EU, US-FDA, and China are 100 μg/kg [ 4 ]. Unfortunately, sulfonamides are a growing cause of health concern because of its high levels in edible agricultural and food products [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The developed method was used to determine SAs in 100 egg and 3 positive egg samples from an animal study for further validation [ 34 ]. Positive results were analyzed in accordance with the standard method of China and this method (SN/T 4057-2014) [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 100 egg samples were acquired from different markets and poultry farms. Positive samples for the control group were obtained from animal experiments [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, special laboratories with expensive equipment and high-quality personnel were demanded. Obviously, the application of these methods in on-site detection of antibiotic residues in food was limited ( Suo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%